Uterine rupture complicating sequential curettage and Bakri balloon tamponade to control secondary PPH - Ajayi, Olukunle Adegboye (BMJ Publishing Group, 2013)
A 20-year-old para 2 woman had a preterm delivery at 25 weeks and 6 days, readmitted to the hospital 25 days after delivery with severe secondary postpartum haemorrhage (PPH). Uncontrolled by initial conservative management, she underwent uterine curettage followed by Bakri balloon tamponade. She later had laparotomy for continued bleeding. She was found to have uterine rupture and hysterectomy was carried out as a life-saving measure. She was transfused in total with 14 units of blood, 1 unit of platelet, 2 units of cryoprecipitate and 3 units of fresh frozen plasma. The patient had intensive therapy unit  care and was discharged home on the sixth postoperative day. The histology report showed ectatic non-constricted vessels as the cause of the secondary PPH. No myometrial tissue, products of conception or evidence of endometritis. The sequential use of uterine curettage and balloon tamponade in the aetiology of uterine rupture is a rare occurrence.